An integrative counselling program to promote active ageing for older people in Thai nursing homes: an intervention mixed methods design - Jantana Juthavantana; Nanchatsan Sakunpong; Ujsara Prasertsin; Monthira Charupheng; Sheibon Hassakama Lau (BMC Psychology, 2021)
Abstract Background Active ageing has been a rapidly developing field of study in light of the growing population of older people. Acknowledgement of the lack of a counselling program to promote active ageing for the older people in nursing homes led to the development of this study which aims to investigate active ageing of the Thai elderly in a nursing home in addition to promoting active ageing for them through integrative counselling. Methods The study was conducted in a nursing home in Samut Prakan province, Thailand. The integrative counselling program referred to appropriate literature along with implementation of the Satir Model and Motivational Interviewing techniques. An intervention mixed methods design was applied in the study, which consisted of two phases. Phase 1 involved an investigation of the concept of active ageing, based on the context of older people in nursing homes by way of in-depth interviews, involving 5 participants. Phase 2 comprised of an investigation of the effects of an integrative counselling program to promote active ageing for older people in the same nursing home. There was a total of 16 participants in phase 2 which were divided equally into experimental and control groups respectively. Results Phase 1 of the study showcased qualitative results of the progress of active ageing development in older people that resulted in 4 sub-themes (Health development, spiritual development, active engagement and psychosocial support). Two parameters were used to analyze the results in phase 2. The quantitative results showed that the active ageing score of participants in the experimental arm increased significantly after enrollment (p < 0.05). Furthermore, the experimental group had a higher overall active ageing score in comparison to the control group. Qualitative results of phase 2 elicited factors promoting active ageing in the elderly which included activities, group facilitator and group atmosphere. Both quantitative and qualitative results of phase 2 proved to be significant, showing that the program managed to develop active ageing in participants. Conclusion Psychologists and multidisciplinary teams looking after older people in nursing homes are able to use this integrative counselling program for development of active ageing in the elderly population.